Nose-to-Brain Drug Delivery: An Update on Clinical Challenges and Progress - Gangane, Purushottam; Raulkar, Nikita; Wagh, Nikita; Rabade, Vijaya; Sawarkar, Harigopal (Indian Journal of Pharmaceutical Education and Research, 2025)
In 1987 James Parkinson first describes Parkinson's Disease (PD) as a neurological syndrome. Over ten million people worldwide suffer with PD. The exact quantity of people suffered with PD is difficult to calculate because many people are not diagnosed in the early stages of the disease. As people age, they are more probable to develop PD. After Alzheimer's disease, it's the second utmost common age-related neurodegenerative condition. PD is a common prevalent neurological illness that causes significant disability. Dopaminergic neuron malfunction in the substantia nigra compacta characterizes the diseased condition. The cardinal clinical symptoms of akinesia, stiffness, tremor and autonomic dysfunction distinguish it. Oral medications may lose their effectiveness in the treatment of PD because a number of factors such as dysphagia, impaired absorption from the gastrointestinal tract and delayed stomach emptying. Intranasal therapy may be considered to alleviate this problem. As a new approach to treating central nervous system disorders, the intranasal route of medication administration is being explored. It is a novel delivery method that may circumvent these issues, allowing Glial cell line-Derived Neurotrophic Factor (GDNF) to reach the brain and halt the progression of PD. Different nanocomposites can be delivered intranasally to treat PD.
Keywords: Parkinson’s disease; Nasal cavity; Nose-to-brain drug delivery